Reciprocity in International Business: A Study of Telecommunications Alliances and Contracts - Kashlak, Roger J.; Chandran, Rajan; Anthony Di Benedetto, C. (Journal of International Business Studies, 1998)
Reciprocity has been identified as a “messy” concept to study within international cooperative ventures. Theoretically grounded in international cooperation, transaction cost theory and economic anthropology, reciprocity is operationalized and explored in this study. Specifically, the effects of cultural distance, economic nearness, country-level risk and governance mechanisms are analyzed in relationship to three distinct measures of reciprocity. The international long distance industry provides the research setting. During the 1980s and 1990s, as this industry has become more competitive within the United States, foreign partners have been slow to reciprocate regarding the sharing of revenues derived from increased overseas calling. To study reciprocity between U.S. international long distance carriers and their partnering foreign entities, a pooled time-series/cross-sectional technique is used. 11 years of contractual arrangements between the U.S. firms and the telecom administrations of 109 countries are analyzed. Governance mechanisms test as highly significant with all measures of reciprocity, while the other independent variables exhibit varying degrees of significance with the respective dependent measures.